Modelagem de processos de negócio: um comparativo entre BPMN e UML - Szilagyi, Daniele Chrusciak (2010)
Considering that all organizations have a purpose, which involves services performing or products generation its necessary understanding and establishing the activities set needed to accomplish this goal. This activity set is known as process. The process modeling appear as an opportunity to improve these processes before being automatized, proportionating the analysis and the redesign of them, identifying and correcting their fails, redundancies and bottlenecks. This work presents the importance of the business process modeling technique in order to aid the correct understanding of the customer business process. It will be presented the benefits and advantages of business process modeling notation BPMN, in comparison with the business modeling from UML